THE EXPERIENCE OF DEVELOPED COUNTRIES IN REGULATING THE USE OF REMOTE PERSONNEL LABOR - Sitora SHOISLOMOVA (Scholar Express Journals, 2022)
The research focuses on the concepts of “remote work”, “remote worker”, the introduction of remote work, the features of the procedure for interaction between a remote worker and the employer, the regulation and organization of labor of remote workers devoted to the study of aspects. The study also examines the approaches to regulating the work of teleworkers in the legislation of foreign countries, and in this regard develops important proposals and recommendations for improving the legislation of the Republic of Uzbekistan
Keywords: remote work; remote worker; introduction of remote work; regulation